Succinato de ródio (II): síntese, caracterização e adsorção em nanopartículas de maghemita - SILVA, Matheus Oliveira da (2012)
In this work it was described the synthesis and characterization of rhodium(II) succinate complex unpublished and adsorption study in maghemite nanoparticles. The rhodium(II) succinate was synthesized from a precursor rhodium(II) carboxylate, rhodium(II) trifluoracetate with a yield of 48.2%. The complex has become completely soluble in aqueous medium only when neutralized with 0,01 molL-1 NaOH solution to produce the sodium rhodium(II) succinate. The complex was characterized as the composition and structure by C and H elemental and thermogravimetric analysis, potentiometric titration, infrared and UV/visible spectroscopy. The data agree with a dimeric structure with four free carboxyl groups and suggest the molecular formulas [Rh2(O4C4H5)4(H2O)4] and [Na4Rh2(O4C4H4)4(H2O)5] to the rhodium(II) succinate and sodium rhodium(II) succinate respectively. Magnetite nanoparticles in aqueous media was prepared by coprecipitation method of Fe2+ and Fe3+ ion which was oxidized with oxygen gas. The solid obtained was characterized as crystalline phase by X-ray diffraction and as structure by infrared spectroscopy. The mean diameter of the nanoparticles (8 nm) was calculated by the Sherrer equation and lattice parameter was obtained through UnitCell program. It was obtained adsorption isotherm witch profile suggests the formation of multilayer adsorption having physical and chemical adsorption. The chemical adsorption was confirmed by infrared spectroscopy. The experimental data corresponding to monolayer were best fitted by the Freundlich adsorption isotherm with linear coefficient, R2, equal to 0,965. The functionalized nanoparticles were evaluated by measuring colloidal stability through hydrodynamic diameter and their surface properties by zeta potential measurements. The data showed strong dependence of the shifting of the IEP and the range of colloidal stability as a function of the amount of adsorbed complex and pH.